Digital Literacy in the Help of Education - Emilov, Iliya (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
A survey has been conducted with teachers and students in two private schools in Bulgaria to observe the digital literacy used in education recently. The aim of the study is to detect the digital skills of the participants and to take a snapshot of the atmosphere of online educational process. In teaching and learning process, the nature of learning environment is important. According to Piaget and Vygotsky, the social interaction has a key role in formation of cognitive development of students. Providing constructivist learning environment at schools will help learners to increase their attitudes towards the taught subjects. ICT has an important role in building such an atmosphere where students can develop their digital skills in using different strategies such as inquiry-based learning, problem-based learning, discovery learning, etc. Today there are plenty of digital platforms that are used in teaching, learning and evaluation processes. In one year, after the pandemic, schools started to use different Learning Management Systems. Our lives have changed spontaneously with the new style of learning and teaching models. Although those platforms existed before the pandemic, their usage was at a very low level. The schools, teachers and educators with up-to-date qualifications, did not have any turbulences in adapting their skills in new situations, which are in the base of constructivist approach.